Keeping distance with a telepresence robot: A pilot study - Leoste, Janika; Heidmets, Mati; Virkus, Sirje; Talisainen, Aleksei; Rebane, Martin; Kasuk, Tiina; Tammemäe, Kalle; Kangur, Katrin; Kikkas, Kaido; Marmor, Kristel (Frontiers in Education, 2023)
Introduction Telepresence robots (TPRs) are the subject of an emerging field of application and research that has recently received attention from various disciplines. Most of the relevant research has been done in computer science, while the interest from psychology and education has been relatively modest. Proximity plays an important role in personal interactions. Although human spatial behavior has been widely studied in social psychology, little attention has been paid to the spatial behavior of humans and TPRs. Methods The purpose of this paper is to present the results of a pilot study that investigated a certain aspect of spatial behavior – physical proximity or interpersonal distance – based on four social zones of interpersonal distance that characterize Western culture: intimate, personal, social, and public. The study conducted an experiment involving participants both in person and via TPRs, using the Double 3 TPRs in various simulated situations. Results According to the findings, when interacting with a TPR, most participants maintained a communication distance of 60 to 160 cm, which is the borderline between personal and social distance, quite similar to normal human-to-human social communication. Status and previous relationship did not play any role in the choice of communication distance, but there were significant gender differences. On average, male participants chose a shorter distance to interact with TPRs compared to female participants. Persons with previous computer gaming experience chose a significantly shorter communication distance compared to persons with no such experience. A little more than half of the participants found the method of communication through TPRs to be pleasant. Discussion TPR mediated persons might be perceived as “real” when communicating with physically present persons, with similar norms applied as in human-to-human social interactions. Especially in the context of classroom communication, people keep communication distances comparable to far personal or close social distances. These findings suggest that implementation of TPRs in education does not put additional requirements for physical space in classroom.